2009
DOI: 10.1080/00016480802163358
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin treatment induces morphology alterations and apoptosis in murine cochlear neuronal cells

Abstract: Simvastatin caused a loss of the cytoplasmic projections in VOT-33. In primary rat cochlear nerve cells, simvastatin decreased staining for NF200, a neuro-cytoskeletal protein. We also found that simvastatin-induced VOT-33 apoptosis, as indicated by accumulation of the sub G0/G1 fraction, DNA-ladder formation, and caspase-3 activation. The above-mentioned effects were abolished by mevalonate treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…The nerve fiber damage was extensive in rats receiving 80 mg/ kg. The effects of statins on the nervous system are controversial, since some authors suggest neuroprotective effects whilst others have demonstrated that statins induced neuronal apoptosis [23]. A study conducted by Otruba et al, [24] confirmed definite damage to peripheral nerves in patients taking statins for more than 2 years.…”
Section: The Morphometric Resultsmentioning
confidence: 88%
“…The nerve fiber damage was extensive in rats receiving 80 mg/ kg. The effects of statins on the nervous system are controversial, since some authors suggest neuroprotective effects whilst others have demonstrated that statins induced neuronal apoptosis [23]. A study conducted by Otruba et al, [24] confirmed definite damage to peripheral nerves in patients taking statins for more than 2 years.…”
Section: The Morphometric Resultsmentioning
confidence: 88%
“…Taken together, these results implicated that mevalonate does not play a major role in simvastatin-mediated protection. Simvastatin at higher doses has been shown to alter cellular morphology (41,42). Although the biological significance of simvastatin-induced cellular morphological changes varies depending on cell type, we took this as one measure to evaluate the cellular uptake of mevalonate in airway epithelial cells.…”
Section: Mevalonate Supplement Does Not Abrogate Simvastatin-conferrementioning
confidence: 99%
“…Accordingly, simvastatin does not only trigger apoptosis, the suicidal death of nucleated cells [31-39], but by the same token triggers eryptosis, the suicidal erythrocyte death. The simvastatin concentrations required for the stimulation of eryptosis were in the range of concentrations (0.9 µg/ml) measured in the plasma of patients [39].…”
Section: Discussionmentioning
confidence: 99%
“…Simvastatin has been shown to stimulate apoptosis of neurons [31] and tumor cells [32-39]. In view of its effect in tumor cells simvastatin was considered as a potential therapeutic option in malignancy [32, 35-37].…”
Section: Introductionmentioning
confidence: 99%